2014
DOI: 10.1155/2014/182303
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Biomarkers of Oxidative Stress and Antioxidant in Alzheimer’s Disease: A Systematic Review

Abstract: Purpose. Oxidative stress plays an important role in the pathogenesis of Alzheimer's disease (AD). This paper aims to examine whether biomarkers of oxidative stress and antioxidants could be useful biomarkers in AD, which might form the bases of future clinical studies. Methods. PubMed, SCOPUS, and Web of Science were systematically queried to obtain studies with available data regarding markers of oxidative stress and antioxidants from subjects with AD. Results and Conclusion. Although most studies show eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
116
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 75 publications
(166 reference statements)
2
116
0
2
Order By: Relevance
“…During aging, however, there is a clear accumulation of free radicals and associated damage in various tissues [17][18][19] -and this constitutes the basis for the free radical theory of aging. In addition, enhanced oxidative stress (OS) contributes to the pathogenesis of many age-related diseases [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…During aging, however, there is a clear accumulation of free radicals and associated damage in various tissues [17][18][19] -and this constitutes the basis for the free radical theory of aging. In addition, enhanced oxidative stress (OS) contributes to the pathogenesis of many age-related diseases [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There is consistent evidence in literature showing the involvement of free radical-induced oxidative damage in the etiopathogenesis of AD, since oxidative stress is one of the earliest events in AD pathogenesis [18,[80][81][82]. Moreover, oxidative damage has been shown in the blood, CSF and brain of neurological patients with probable AD [83][84][85]. Post mortem studies on brain specimens collected from individuals affected by AD, evidenced extensive oxidative stress compared to healthy controls, i.e.…”
Section: Involvement Of Sam In Oxidative Stress and Neurodegenerationmentioning
confidence: 52%
“…Menopause is associated with an increase in oxidative stress, resulting from an imbalance between reactive oxygen species (ROS) and the antioxidant system (3)(4)(5). Previous studies have demonstrated that oxidative stress is implicated in the pathogenesis of various chronic diseases (6)(7)(8)(9). Osteoporosis is a skeletal disorder characterized by compromised bone strength, predisposing patients to increased risk of fracture (10).…”
Section: Introductionmentioning
confidence: 99%